(untitled) (Baghdad Science Journal, 2008)
The drug promethazine hydrochloride (PRZH) forms with rhodium (II) a colored chelate (?max = 472 nm) complex at (pH = 2.1) which is extractable with benzyl alcohol as organic solvent. Under the appropriate experimental conditions a calibration plot was set up from which some analytical parameter were derived and deduced by regression. Standard addition procedure was also adopted. It has been estimated that the concentration of the drug PRZH to be 24.89 mg per unit and 24.19 mg per unit for both calibrations. Under optimal conditions, the developed method has been achieved the following characteristics: LDR (30 – 150 µg ml-1 ) PRZH , RSD % ( 0.6 – 2.47 ) , sandell sensitivity( 0.0844 µg. cm -2 ) , LOD ( 1.66 µgml-1 ) , recovery % ( 100.74 ± 1.34 ) , Erel % ( 0.74 ) . Stability constant (6.4 × 10 5 M-1). The mole – ratio method (1: 1) approved that PRZH – Rh (II) as a structure of the complex. The developed procedure has been adapted to analyze PRZH in various pharmaceuticals.